(untitled) (Ibrahim Cardiac Medical Journal, 2023)
Background & objective: Septic abortion still remains one of the most serious threats to the health of women all over the world. Most women indulge in unsafe abortion, for they no longer want children, but failed to take any contraception. The present study was undertaken to describe their clinical presentation, management and outcome including maternal complications and mortality caused by induced septic abortion. Methods: This descriptive study was conducted in the Department of Obstetrics & Gynaecology in Dhaka Medical College Hospital, Dhaka, Bangladesh over a period of 6 months between July 2008 to December 2008. All patients with septic abortion up to 28 weeks of gestation admitted to the Department of Obstetrics & Gynaecology at Dhaka Medical College Hospital (DMCH) were the study population. Patients with induced septic abortion with signs of infection were included in the study. However, patients with inevitable abortion, missed abortion, spontaneous septic abortion and septic abortion with the medical disorder were excluded from the study. A total of 50 patients based on above-mentioned eligibility criteria were included in the study. Data were analyzed to describe their clinical presentation, management and outcome, which among others included maternal complications and mortality. Result: Almost three-fifth of the patients were in their 3rd decade and 26% in their 4th decade of life with mean age of the patients being 27.2 ± 1.6 years. Over 40% were primary level educated and a sizable portion (36%) was illiterate. Majority of the patients was married (96%), house-wife (82%), rural resident (76%) and belonged to poor socioeconomic class (80%). More than 60% of the patients were in 2nd trimester of pregnancy and over two-thirds (68%) were multipara. For initiating abortion, about one-third (32%) used stick inside the vagina, 24% received menstrual regulation, 14% underwent D & C (dilatation & curettage), 22% took oral medication. More than one-third (36%) of the patients aborted for their pregnancy was unwanted, 20% did it because their pregnancy was unplanned. A few patients however mentioned social problem (6%) and husband’s illness (2%) as the reasons of induced abortion. The lower abdominal pain (96%) and per vaginal bleeding (94%) were the predominant complaints of the patients followed by followed by fever (72%), discharge of foul-smelling lochia (68%) and abdominal distension (12%). On examination majority (96%) was found anemic, toxic (56%), feverish (82%), with lower abdominal tenderness (60%) and dehydration (50%). On local examination, 80% exhibited signs of bleeding with tender fornics. Open external os, dirty vulva and foul-smelling discharge were observed in 74, 60 and 30% of the cases respectively. Vaginal and cervical injuries were found in few cases. More than 90% of the patients improved and cured and 8% died of complications like generalized peritonitis (2%) and septicemia with renal failure (6%). Conclusion: Induced septic abortion patients are generally multipara and present in 2nd trimester of pregnancy. In one-third of cases, the stimulus used to initiate abortion is stick inside the vagina. Other procedures adopted are menstrual regulation, D & C, oral ingestion of abortifacient drugs etc. Reasons of abortion include unwanted or unplanned pregnancy. While the cardinal symptoms at presentation are lower abdominal pain and per vaginal bleeding, cardinal signs are anemia, raised temperature and lower abdominal tenderness. Local examination usually exhibits signs of bleeding with tender fornics, open external os. Vaginal and cervical injuries are sometimes present. Majority of the patients cure on conservative treatment. Some however, require operative treatment. Very few patients died of complications (peritonitis and septicemia with or without renal failure) of the disease. Ibrahim Card Med J 2022; 12 (1): 58-63